Tempos de resfriamento e aquecimento: repercussão no desempenho da manutenção na indústria siderúrgica - Reis, Rubens Alberto dos (2009)
The goal of this study is to analyze the effects of equipment cooling and heating times in the indicators used to evaluate the maintenance performance. In the case study it has been verified the need for a more detailed description and deployment of the indicators in order to include these times. The study showed that in this case, depending on the size of the heat factor in the production process, the maintenance team changes its practices and increases interaction, strengthening mutual aid as it enhances the sharing of responsibility. In this conception of work, action planning and evaluation of the consequent results are both aimed at integration, interactin and co-responsibility for the productivity, quality, reliability and security of the plant. The research showed that the times of cooling and heating are not considered in isolation. In the case of a corrective maintenance the total time of intervention is recorded. The responsibility for the failure may be the industry’s maintenance or production, according to its cause.